Aborto e o direito constitucional à vida - Borges, Indiana Velho (My University, 2020)
The present work of conclusion of course aims to offer an overview about abortion, its modalities, abortion and its evolution through history, fundamental rights and guarantees, a brief analysis of individual rights, the crime of abortion in the Brazilian Penal Code and when needed. The subject matter of this study caused, causes and certainly will still cause a lot of controversy for a long period, generating debates that hardly reach a consensus, that is, abortion. In addition to these factors, it is known that abortion is practiced in a clandestine manner, causing several serious consequences, both physical and psychological, among others (sic).
O presente trabalho de conclusão de curso visa oferecer uma visão geral a respeito do aborto, suas modalidades, o aborto e suas evoluções através da história, os direitos e garantias fundamentais, uma breve análise dos direitos individuais, o crime de aborto no Código Penal Brasileiro e quando necessário. O tema objeto deste estudo causou, causa e seguramente ainda causará muita polêmica por um longo período, sendo gerador de debates que dificilmente atingem um consenso, qual seja, o aborto. Além desses fatores sabe-se que há o aborto praticado de forma clandestina provocando diversas consequências graves tanto físicas como psicológicas entre outras (sic).
Keywords: Aborto; Direito constitucional; Crime